Virgin coconut oil and palm tocotrienol supplementation: effects on lipid parameters of experimental rats - Norhayati-Aida Sulaiman,; Azman Abdullah,; Thent, Zar Chi; Qodriyah Mohd Saad, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Virgin coconut oil (VCO) and palm tocotrienol (TT) possess cholesterol-regulating properties, but their combined effects remained unexplored. Thus, this study aims to determine their individual and combination effects on lipid parameters in ovariectomised (OVX) rats on hypercholesterolemic diet. Female Sprague-Dawley rats were ovariectomised except for the sham group, assigned into (i) sham-operated fed with basal rat diet, (ii) OVX control, (iii) V1 (OVX + VCO 1.43 mL/kg), (iv) V2 (OVX + VCO 4.29 mL/kg), (v) TT (OVX + TT 30 mg/kg), (vi) V1+TT (OVX + VCO 1.43 mL/kg + TT 30 mg/kg) and (vii) V2+TT (OVX + VCO 4.29 mL/kg + TT 30 mg/kg). Groups (ii) to (vii) were fed with 2% cholesterol mixed with five-time heated palm oil. VCO and TT alone or in combination reduced food intake, visceral fat weight, thiobarbituric acid reactive substances and HMG-CoA reductase activity significantly (p<0.05) vs the OVX control). HDL was reduced significantly in V1, V2, and V1+TT compared to the TT and V2+TT (p<0.05). The increase in LDL was the lowest in V1 compared to other groups (p<0.05). V2 and TT significantly reduced total cholesterol compared to other supplementations (p<0.05). All supplementations were found to reduce triglyceride compared to the OVX control group (p<0.05). The increase in apolipoprotein A was higher in V2+TT than other groups (p<0.05). The reduction in apolipoprotein B was higher in V1+TT and V2+TT than the V1, V2 and TT. VCO and TT exerted beneficial effects on lipid parameters, but the efficacy was not better than individual agents.